Smartcanteen: Transforming canteen ordering with a mobile application - Kaviraj, Maniveel (2024)
The traditional paper-based ordering system used in most Malaysian canteens has been unchanged for almost five decades, with extremely manual and time-consuming operations that cause bottlenecks and reduce productivity. Long lineups during peak hours, a lack of menu visibility, numerous order problems, and limited payment alternatives have all contributed to an unfavourable shopping experience for students, staff, and management. This project seeks to address these long-standing inefficiencies by creating a new mobile application, “SmartCan-teen,” that uses cutting-edge technologies and user-centric design concepts to revolutionise the canteen ordering process. The proposed solution takes a complete approach, including features like remote pre-ordering, digitised menus with real-time availability updates, automated order processing to reduce errors, and interaction with a variety of electronic payment options. The “SmartCanteen” app aims to improve efficiency, sustainability, accessibility, and overall cus-tomer pleasure by streamlining operations, increasing transparency, and optimising staffing us-ing data-driven insights. The project's methodology includes a thorough literature research to obtain knowledge about existing systems, technologies, and best practices. Following that, a user-centric design strategy is used, which includes active user interaction and iterative feed-back loops to ensure alignment with organisational goals and preferences. The development phase focuses on iteratively refining prototypes based on user feedback, using technologies like Android Studio and Firebase to provide smooth integration and data management. The “SmartCanteen” project offers a big step towards modernising Malaysia's canteen ordering ex-perience. By tackling the highlighted difficulties with an innovative and complete solution, it provides a creative way to streamlining operations, increasing customer happiness, and boost-ing operational efficiency in the field of campus dining experiences.